Study on Cadmium Complex Reaction with p-Acetyl Benzenediazo- aminoazobenze and Determination of Trace Amounts of Cadmium by β-correction Spectrophotometry - Li, Mei; Ye, Ming-Liang; Gao, Hong-Wen (Asian Journal of Chemistry, 2010)
The synthesis of ligand, p-acetyl-benzenediazoaminoazobenzene (p-ABAA) was carried out and its complex reaction with cadmium was sensitive in basic solution and in the presence of the nonionic surfactant, emulsifier OP Because of the effect of excess of p-ABAA on the absorption of Cd-p-ABAA complex product, the ordinary spectrophotometry was limited for use. The current principle, named β-correction theory was applied instead of single wavelength method. It gave the simple determination of the composition ration, molar absorptivity (ε) and stability constant (K) of Cd-p-ABAA complex. Results showed that complex Cd(p-ABAA)3 was formed at pH 12.5, its real (not apparent)molar absorptivity was 1.28 x 105 L mol–1 cm–1 at 475 nm and its cumulative stability constant 7.78 x 1018. For analysis of water samples, the recovery of cadmium was between 98.5 and 110% and the relative standard deviations less than 7.1 %.